SEJARAH PEMBENTUKAN UNDANG-UNDANG DASAR SEMENTARA (UUDS) 1950 SAMPAI DIKELUARKANNYA DEKRIT PRESIDEN 5 JULI 1959 DI INDONESIA - Khatijah Army; Drs.Ridwan Melay, M.Hum; Drs.Marwoto Saiman, M.Pd (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:The Changes in the Constitution Republic of Indonesia in the science of law is called the amendment of the Constitution that has been done four times has affected substantially and basically has changed state system of Indonesia. After Indonesia's independence in 1945, the legal system does not has changed. At the 1950 to 1959, Indonesia using the Temporary Constitution 1950 as the basis country. The temporary constitution began on August 17, 1950 until the birth of the decree of the President on July 5, 1959 issued by President Soekarno. This research have a purpose to know about (1) the background of the formation of the Temporary Constitution 1950 in Indonesia. (2) the process of implementation of the the Temporary Constitution 1950 in Indonesia. (3) the end of the 1950 the Temporary Constitution after the issuance of Presidential Decree of July 5, 1959 in Indonesia. This research use a qualitative method with approach history and data collection techniques in the form of literature and documentation. The results of this research indicate that the period of the Temporary Constitution 1950 was also marked by the process of dissent and discord. The split occurred in the political parties. Then followed the ideological conflict between the political parties. Consequently, there is an unstable political situation so that at the time this happened in 1950 the Temporary Constitution seven changes from the cabinet for nine years.Keywords: The Temporary Constitution 1950, The Presidential Decree July 5, 1959